Analysis ratio finance in sector BUMN companies construction listed on BEI - Alfianita, Devi; Fahriani, Dian (Enrichment : Journal of Management, 2023)
Financial ratio analysis is a method for quickly finding out the financial performance of a company, this also applies to construction companies. Financial ratio analysis that is of the used to assess a company’s financial performance is liquidity ratio analysis, solvency ratio analysis and profitability ratio analysis. Bursa Efek Indonesia noted that there were 23 construction companies there were 23 construction companies that had joined, among the 23 companies there were 4 state-owned companies, namely PT Waskita Karya, Tbk., PT Wijaya Karya, Tbk., PT Pembangunan Perumahan, Tbk., and PT Adhi Karya, Tbk. Thid research uses state-owned companies in the construction sector as research samples. The research method used is a qualitative method through descriptive analysis and in-depth observation. Tha aim of this research is to determine the financial performance of 4 state-owned companies in the construction sector so that companies with the best financial performance can be found. Based on results from study ratio finance in 2020-2022 which uses calculation ratio liquidity, ratio solvency and ratios profitability show that performance finance company experience fluctuation